math

posted by .

What ia A inverse if A = (3 -2)
(3 2)

  • math -

    for
    a b
    c d

    for a denominator let k = ad - bc
    If k is zero, there is no inverse

    k = 6 - (-6) = 12

    the inverse is

    d -b
    -c a times 1/k

    we would ge
    (1/12) times the matrix

    2 2
    -3 3

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. inverse

    find f^-1 (x). (this is asking me to find the inverse) f(x) = -(x-2)^2, x <= 2 how do I solve this problem?
  2. Pre-Calc

    Does y=1/x have an inverse? It is a one-to-one function, so it should be the inverse equation is the same?
  3. math

    The cost of producing q articles is given by the function C=f(q)=100+2q. (A) Find the formula for the inverse function. (B) Explain in practical terms what the inverse function tells you. I am pretty sure the answer to A is f^-1(C)=C/2-50 …
  4. Very easy math

    my teacher told me that the inverse of addition was subtraction and that the inverse of subtraction was addition... could you prove it to me -x = (-1)x ((-1)x)^-1 I don't see how I'm suppose to get + x by taking the inverse of -x i've …
  5. math

    Determine the inverse of f(x)=(x^3)-2 Is the inverse the switch of coordinates between x and y or is it 1 over the whole equation?
  6. Algebra

    what is the inverse of the linear parent function?
  7. Pre-caluclus

    I do not know how to solve for y to get the inverse of this question: The number of elephants in a park is estimated to be P(t)=7500 1 + 749e^(−0.15t) where t is the time in years and t = 0 corresponds to the year 1903. Find …
  8. Advanced Algebra

    What is the inverse of each of the functions defined by the following equations, if the inverse exists. If the inverse does not exist for the largest possible domain, limit the domain so that the inverse will exist. In each case, give …
  9. Math

    Find inverse of f if f(x)= x^2-4x+3, (for x is smaller than and equal to 2). First prove that f(x) is one to one in the defined domain of f and then obtain the inverse function. I know how to find the inverse. We just switch x and …
  10. Math- steve? reiny?

    1. Let f(x)=x^5 + 2x^3 + x - 1 Find f^-1(3) and (f^-1)'(3)?

More Similar Questions